Penilaian Tingkat Kepuasan Masyarakat Terhadap Pelayanan Pada Kantor Wali Nagari Bunga Pasang Salido Menggunakan Algoritma K-Means - Hidayatullah, Genta Magribi; Putra, Ondra Eka; Rahmi, Nadya Alinda Rahmi; Akhiyar, Dinul (Riset Sinergi Indonesia, 2025)
Assessing public satisfaction is crucial for evaluating the quality of services provided by government agencies. The purpose of this study was to analyze public satisfaction with the services provided by the Bunga Pasang Salido Village Head Office. This study used the K-Means algorithm, a clustering technique commonly used in data analysis, to categorize respondents' satisfaction levels. This algorithm effectively categorizes respondents into categories such as dissatisfied, satisfied, and very satisfied based on their responses in a satisfaction survey. The dataset used in this study was derived from questionnaires completed by 61 respondents who interacted with the population administration service. The questionnaire data covered various aspects of service quality, including service process efficiency, officer attitudes, and overall user experience. The results of the clustering analysis showed that 27.87% of respondents were dissatisfied, 42.62% were satisfied, and 29.51% were very satisfied with the services provided. This classification provides valuable insights into areas for improvement and helps the Bunga Pasang Salido Village Head Office improve service quality. This study highlights the importance of using data-driven methods, such as the K-Means algorithm, in improving public sector performance and overall service quality.